The Mauritius command - O'brian, Patrick (London : Harper Perennial, 2007)
Captain Jack Aubrey, given secret ord4ers to take a frigate to the Cape of Good Hope to mount an expedition against the French-held islands of Mauritius and La Reunion, finds his mission endangered by the behavior of two of his crew members.
Keywords: Aubrey, Jack (Fictional character) -- Fiction; Maturin, Stephen (Fictional character) -- Fiction; Ship captains -- Fiction; Ship physicians -- Fiction; Great Britain -- Naval history -- Fiction